TEORI PERKEMBANGAN BAHASA, PSIKOSOSIAL DAN EMOSIONAL PADA ANAK : DITINJAU DARI PERSPEKTIF PENDIDIKAN ISLAM - Lathifah; Izzatuzzahroh; Salwa Aurumia Firanti; Meleza Andora; Indah Wigati; Fitri Oviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This paper aims to comprehensively review and analyze various theories of language, psychosocial, and emotional development in children, as well as their relevance in the context of Islamic education and character building. This paper is expected to provide a better understanding of this development process and serve as a consideration for educators and parents in educating children. The research method used is qualitative with a library research approach, which consists of theories relevant to the research problem. The data sources in this study are divided into primary and secondary sources. The primary source in this study is the book that is the object of this study. Secondary sources are additional data sources that, according to the researcher, support the main data. The results of the study show that language, psychosocial, and emotional aspects are closely related and influence each other. Deficiencies in language development, such as difficulty communicating or expressing oneself, can affect a child's social-emotional development. Conversely, social-emotional maturity enables children to use language more effectively in interactions.